Evaluation of pressure- and electrodriven separation techniques for the determination of phenolic compounds in wine - De Villiers, A. J. (Andre Joubert) (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.